Implementation Of The Preceptorship Model In Midwife Care: Scooping Review - Ana Dyah Aliza; Farida Kartini (Universitas 'Aisyiyah Yogyakarta, 2021)
Background: The Preceptorship model has different rules in clinical practice learning for health students at a midwifery clinic. The purpose of this literature review is to find out the perspective of the implementation of preceptorship from various groups of student education levels on midwifery care as a whole. Method: This article takes databases from PubMed, Wiley, Google Scholar, and ScienceDirect published between 2010-2019 with the keywords